Cosmetic Surgeon Representation: Ensuring Board Certification Transparency and Patient Awareness. (June 2018) - Tessler, Oren; Bourn, Lynn; Lin, Samuel J.; Dupin, Charles; Mundinger, Gerhard S.; Patterson, Charles; St. Hilaire, Hugo; Bartow, Matthew; Torabi, Radbeh; Hanemann, Michael
Abstract : Background: Previous studies revealed that patients preferred plastic surgeons over cosmetic surgeons for surgical procedures, but few knew that any physician with a medical degree was legally qualified to perform cosmetic surgery. Results also indicated that a primary consideration for patients in selecting a surgeon was board certification. Although patient preferences concerning aesthetic surgery have previously been surveyed, no study examined a consumer's ability delineate between specialties based on Web sites. The purpose of this study was to investigate the responses of medical students to questions regarding a cosmetic and plastic surgeon's board certification. Methods: A total of 4 cosmetic and 5 plastic surgeon Web sites were selected, in a single large city, from a Google search for the following procedures: liposuction, breast augmentation, blepharoplasty, rhytidectomy, and abdominoplasty. Screenshots of the Google search link, the page after clicking on the link, and the about the doctor page were collected to simulate an actual patient search experience. Four randomized surveys were created using screenshots and scenarios through Survey Monkey. Surveys were distributed and collected anonymously. Data analysis was accomplished using a chi-square test of independence ( P < 0.05). Results: A total of 474 medical students responded, and the difference between cosmetic and plastic surgeon variables was significant ( P < 0.001). Upon comparison of different procedures, the cosmetic and plastic groups were found to be statistically different ( P < 0.05), with some exceptions. On average, when presented with a plastic surgeon, 95.3% thought this was a board-certified plastic surgeon. When presented with a cosmetic surgeon, 54.3% also thought this was a board-certified plastic surgeon. The decline in responses regarding board certification, for the first and second cosmetic surgeons presented, was found to be statistically different ( P < 0.0001). Conclusions: Over 50% of medical students had difficulty distinguishing between a cosmetic and plastic surgeon based on Web site advertisements; therefore, patients may have a more difficult experience. Results of this study prove the need for a universal definition, and patient education, relating to board certifications.